Konflik Disintegrasi Di Indonesia Dan Dampaknya Bagi Nasionalisme Bangsa Indonesia - Muhammad Dani Putra Wijaya; Rhesty Panca Mei Saputri; Agus Danugroho (Antroposen: Journal of Social Studies and Humaniora, 2023)
This paper analyzes the national disintegration conflict and how it impacts nationalism. Nationalism is very important in maintaining the integrity of a nation because basically it is a national ideology that teaches love for the motherland and the people. It can be seen that Indonesian nationalism is currently facing big challenges such as the frequent occurrence of KKN which are spread throughout the country, the uncontrolled entry of foreign cultures, and the loss of confidence in the nation and its own country. The nationalism of the Indonesian people is currently experiencing changes both in terms of challenges and development compared to the past. The method used in this research is descriptive qualitative. In this case, researchers interpret and explain the data obtained by researchers from interviews, observation, documentation, so as to get answers to problems in detail and clearly. The results of this paper show that nationalism can be realized according to the abilities of each individual. Initially, the ideology of Pancasila as the basis of the state with the motto Bhineka Tunggal Ika was believed to tend to unite existing differences. There are many ideologies that already exist in this country that have received public support. Interaction between people of different ethnicities, religions and classes is easy to establish. is closely related to the understanding of differences of opinion with each other, as shown by the cooperation between different tribes which can be easily carried out with rational considerations. But the phenomenon of collapse that starts at the grassroots level is astonishing. The conclusion in this paper is nationalism as an assessment or evaluation of the love for the homeland and the nation for awareness and responsibility as citizens.